Expanding the clinical spectrum of the 16p11.2 chromosomal rearrangements: three patients with syringomyelia - Schaaf, Christian P (Nature Publishing Group, 2011)
16p11.2 rearrangements are associated with developmental delay, cognitive impairment, autism spectrum disorder, behavioral problems (especially attention-deficit hyperactivity disorder), seizures, obesity, dysmorphic features, and abnormal head size. In addition, congenital anomalies and abnormal brain findings were frequently observed in patients with these rearrangements. We identified and performed a detailed microarray, phenotypic, and radiological characterization of three new patients with 16p11.2 rearrangements: two deletion patients and one patient with the reciprocal duplication. All patients have a heterozygous loss (deletion) or gain (duplication) corresponding to chromosomal coordinates (chr16: 29 528 190–30 107 184) with a minimal size of 579 kb. The deletion patients had language delay and learning disabilities and one met criteria for pervasive developmental disorder not otherwise specified. The duplication patient received a diagnosis of autism and had academic deficits and behavioral problems. The patients with deletion had long cervicothoracic syringomyelia and the duplication patient had long thoracolumbar syringomyelia. The syringomyelia in one patient with deletion was associated with Chiari malformation. Our findings highlight the broad spectrum of clinical and neurological manifestations in patients with 16p11.2 rearrangements. Our observation suggests that genes (or a single gene) within the implicated interval have significant roles in the pathogenesis of syringomyelia. A more comprehensive and systematic research is warranted to study the frequency and spectrum of malformations in the central nervous system in these patients.